Sistem Pakar Dalam Diagnosa Penyakit Kanker Rahim Menggunakan Metode Naïve Bayes dan Certainty Factor - Yendrizal Yendrizal (STMIK Budi Darma, 2021)
The uterus is one of the reproductive organs, namely the mouth of the uterus which is very susceptible to cancer and very often women experience cancer due to a lack of health care. suffered by women in the uterus can be like cysts, cervical cancer, uterine cancer, vaginal cancer and others, cancer is also very difficult to cure so that patients eventually have to give up and face death. From this it is necessary to make a diagnosis from the beginning in order to minimize the number of deaths caused by cervical cancer which is faced by many women in the world, especially in Indonesia, in diagnosing this disease can use a computer system in collaboration with experts to produce a system called the system. experts as an effort to help solve problems that occur with uterine disease that is being experienced by some women. The results of this study will show the percentage level of disease experienced by patients by 88% with the help of implementing the naïve Bayes method and certainty factory